Pemberdayaan Siswa Sekolah Dasar dalam Meningkatkan Kesadaran Gizi melalui Media Poster dan Kuis Interaktif di Desa Kalirancang - Muhammad Ridhwan Izzuddin; Hafizh Padmadika; Octa Viany Putri; Vira Octaviana Achmad; Rosi Oktavia; Damai Ariani (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Low nutritional awareness and high consumption of unhealthy snacks remain critical issues among elementary school children, potentially affecting their growth and academic performance. This study aims to evaluate the effectiveness of a nutrition education intervention using poster media and paper-based quizzes in improving nutritional awareness among fourth to sixth grade students. The community service activity was conducted by Universitas Sebelas Maret (UNS) students as part of the Kuliah Kerja Nyata (KKN) program in three elementary schools SD Negeri 1, 2, and 3 Kalirancang, Kebumen Regency. A descriptive-evaluative approach was employed through participatory engagement using simple, low-tech educational media to address technological limitations in the school environment. Data were collected from quiz score analyses and participatory observations during the intervention. The results showed a high participation rate (80–90%) and a substantial improvement in students’ cognitive understanding of nutrition, as indicated by the majority of correct quiz responses. However, behavioral observation revealed a noticeable gap between knowledge and practice, as many students continued to consume unhealthy snacks during school breaks. It can be concluded that poster and quiz-based interventions are effective in enhancing students’ nutritional knowledge but are insufficient to alter behavior without supportive environmental and policy interventions at the school level.